The rapid mass calorimeter: A route to high throughput fire testing. (4th May 2017) - Rabe, Sebastian; Schartel, Bernhard
Summary: The rapid mass calorimeter based on reduced‐size specimens is proposed for accelerated fire testing and put up for discussion, particularly for flame retarded polymeric materials. A mass loss calorimeter is combined with a semiautomatic sample changer. Experiments on specimens of reduced size were conducted on poly(methyl methacrylate), poly(propylene), polyamide 66, poly(ether ether ketone), and pine sapwood square samples with edge lengths of 100, 75, 50, 25, 20, and 10 mm. Specimens of 20 × 20 mm 2 were selected to achieve a crucial reduction in specimen size and a measuring protocol developed. A total of 71 different polymeric materials were investigated in the rapid mass calorimeter and cone calorimeter for comparison and several materials with different heat release rate characteristics in the pyrolysis combustion flow calorimeter to test this additional screening method as well. The important fire properties obtained in the rapid mass calorimeter show reasonable correlation with the cone calorimeter results but also with the oxygen index. All in all, the rapid mass calorimeter produces reliable and meaningful results and, despite acceleration and size reduction, still allows for a certain degree of burning behavior interpretation. Material savings of 96% and time savings of around 60%‐70% are achieved compared to measure cone calorimeter.